Acute effect of static stretching on isometric muscle strength performance - Costa Silva, Gabriel Vasconcellos de Lima (2012)
Objective: Verify the acute effect of static muscle stretching on isometric muscle strength. Methods: A total of 25 healthy young subjects with strength training experience randomly participated in the study. A group performed two hand-grip tests preceded by static stretching with range of motion to discomfort point, during 30 seconds. The other group performed the same tests without any exercise before. After 48 hours, the groups have reversed the training protocol. To compare the means of different tests the Student’s unpaired t-test was performed. Results: When only the hand-grip test was performed, a tendency to reduction (p=0.06) was verified in men, and statistical reductions (p≤0.05) in women. Conclusion: The stretching protocol used in present study promoted an acute deficit on isometric strength performance.